The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11138-010-0128-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining social processes with agent-based models

Abstract: Abstract:JEL Classifications: B41, B53, C63 Keywords: agent-based modeling, methodology It is plain that the Austrian revival that began in the 1970s has yet to succeed in convincing the mainstream of the academy to jettison their physics-based mathematical models in favor of the sort of models and forms of argumentation that contemporary Austrians advocate. Agent-based computational modeling is still in its relative infancy but is beginning to gain recognition among economists disenchanted with the neoclassic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Yang and Chandra (2013) suggested that agent-based models are ideal for investigating competition and strategy present in an evolutionary theory of entrepreneurship. Similarly, McKelvey (2004), Nell (2010), Seagren (2011) and Gangotena (2017) suggested that agent-based computation is essential for the study of order formation, as opposed to the study of equilibrium. The model follows Vriend (2002) in that agents make decision by heuristics and McKelvey’s suggestion that processes be identified where agents can make educated guesses[12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang and Chandra (2013) suggested that agent-based models are ideal for investigating competition and strategy present in an evolutionary theory of entrepreneurship. Similarly, McKelvey (2004), Nell (2010), Seagren (2011) and Gangotena (2017) suggested that agent-based computation is essential for the study of order formation, as opposed to the study of equilibrium. The model follows Vriend (2002) in that agents make decision by heuristics and McKelvey’s suggestion that processes be identified where agents can make educated guesses[12].…”
Section: Methodsmentioning
confidence: 99%
“…Agent-based modeling presents an opportunity to integrate creativity into the core of a model of economic activity. Much discussion has focused on this potential without applying the insight or framework to an agent-based model (Nell, 2010; Seagren, 2011; Gangotena, 2017). Newell and Holian (2017) included creativity in an agent-based model in terms of product diversity, but they did not integrate an evolutionary paradigm into their model.…”
Section: Introductionmentioning
confidence: 99%
“…While I have argued that the benefits of computational modeling for entrepreneurship, strategy and strategic entrepreneurship research, especially when grounded in Austrian economics, are many, I have also argued that existing computational models have a long way to go in terms of better aligning their models with the Austrian approach (see also Felin et al, ). An encouraging trend is that the usefulness of computational modeling is increasingly being emphasized within the Austrian economics school itself (Gloria‐Palermo, ; Nell, ; Seagren, ).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…In the absence of such equalities, interaction on the micro level will generate turbulence at the macro level. How much turbulence will accompany the inconsistencies among plans that those inequalities point toward is a topic to be explored, and with some effort to sketch some of this in a framework of agent-based computational modeling set forth in Seagren (2011).…”
Section: Monetary Processes and Central Bankingmentioning
confidence: 99%